WormBase 2016: expanding to enable helminth genomic research. Issue Volume 44:Issue D1(2016) (17th November 2015) - Howe, Kevin L.; Bolt, Bruce J.; Cain, Scott; Chan, Juancarlos; Chen, Wen J.; Davis, Paul; Done, James; Down, Thomas; Gao, Sibyl; Grove, Christian; Harris, Todd W.; Kishore, Ranjana; et al.
Abstract: WormBase (www.wormbase.org ) is a central repository for research data on the biology, genetics and genomics of Caenorhabditis elegans and other nematodes. The project has evolved from its original remit to collect and integrate all data for a single species, and now extends to numerous nematodes, ranging from evolutionary comparators of C. elegans to parasitic species that threaten plant, animal and human health. Research activity using C. elegans as a model system is as vibrant as ever, and we have created new tools for community curation in response to the ever-increasing volume and complexity of data. To better allow users to navigate their way through these data, we have made a number of improvements to our main website, including new tools for browsing genomic features and ontology annotations. Finally, we have developed a new portal for parasitic worm genomes. WormBase ParaSite (parasite.wormbase.org ) contains all publicly available nematode and platyhelminth annotated genome sequences, and is designed specifically to support helminth genomic research.